Pengaruh Model Pembelajaran Kooperatif Tipe Talking Stick Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas IX SMP Negeri 4 Balige Tahun Pembelajaran 2023/2024 - Yesi Asmita Sitohang; Frainskoy Rio Naibaho; Baginda Sitompul; Roida Lumbantobing; Goklas Manalu (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The research aims to determine the positive and significant influence of the talking stick type cooperative learning model on the active learning of Christian Religious Education and Characteristics of class IX students at SMP Negeri 4 Balige for the 2023/2024 academic year. The research hypothesis is that there is a positive and significant influence between the talking stick learning model on the active learning of Christian Religious Education and Characteristics of class IX students at SMP Negeri 4 Balige for the 2023/2024 academic year. The experimental research method has a One Shot Case Study design, namely research by giving treatment to groups or samples and then observing the results. Also uses inferential descriptive quantitative methods. The population of all class IX students at SMP Negeri 4 Balige for the 2023/2024 academic year who are Protestant Christians is 208 people. The sample was determined using a purposive sampling technique (purposeful sample), namely class IX-C, totaling 34 people. The research instruments were closed questionnaires and observations. The results of data analysis obtained: a) The values ​​rcount=0.549>rtabel=0.339 and tcount=3.716>ttable=2.042 indicate a positive and significant relationship. b) Regression equation. c) The determination test shows that the magnitude of the effect is 30.14%. d) Hypothesis testing obtained Fcount=12.281>Ftable=3.32 so H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the talking stick learning model on the active learning of Christian Religious Education and Characteristics of class IX students at SMP Negeri 4 Balige for the 2023/2024 academic year.